ANALYSIS OF FINANCIAL DISTRESS ASSESSMENT USING THE ALTMAN MODEL (ZSCORE) IN FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2021 PERIOD - Birana, Melfi; Nohong, Mursalim; Dewi, Sari (Scientia Integritas Utama, 2022)
This study aims to determine the financial distress assessment of the company The food and beverage subsector is listed on the Indonesia Stock Exchange using the Altman Z-Score model. The sample was selected using purposive sampling method. Seventeen companies in the food and beverage subsector were selected based on criteria listed on the Indonesia Stock Exchange (IDX) and financial reports published regularly for the last five years from 2017 to 2021. Secondary data comes from the website www.idx.co.id. The results show that the Altman Z-Score model can be implemented in detecting the possibility of financial distress in food and beverage subsector companies.there are three companies for five consecutive years in a state of Distress and several in the last two years experiencing financial distress,caused by variable X5 decreased so that sales or income decreased.